Factorization of generalized γ-generating matrices - Sukhorukova, O. (Український математичний вісник, 2017)
The class of γ–generating matrices and its subclasses of regular and singular γ–generating matrices were introduced by D. Z. Arov in [8], where it was shown that every γ-generating matrix admits an essentially unique regular–singular factorization. The class of generalized γ-generating matrices was introduced in [14,20]. In the present paper subclasses of singular and regular generalized γ-a theorem of existence of regular–singular factorization for rational generalized γ-generating matrix is found.